G.i. joe: a real american hero (2023): compendium, volume 1 ebook - Hama, Larry (G.I. Joe: A Real American Hero (2023), 2024)
YOOOO JOE! The pop culture world changed forever when LARRY HAMA's G.I. JOE: A REAL AMERICAN HERO made its comic book debut, and now you can experience every issue—from the original series and tie-ins—in this new reader-friendly compendium format for the very first time. Discover the incredible heroes of G.I. Joe, the terrifying villains of Cobra, and the unforgettable stories that set them on a collision course in this first volume, perfect for fans new and old. Collects G.I. JOE: A REAL AMERICAN HERO #1-50